Financing TB care and control - Fitzpatrick, Christopher; Pantoja, Andrea (Henry Stewart Talks, 2013)
Cost-effectiveness of TB control interventions, Patterns and trends in global TB control financing from the health system perspective, Financing needs for global TB control from the health system perspective, Costs faced by patients in seeking treatment for TB